Tendência da incidência de hanseníase em menores de 15 anos em Jacundá - Pará e sua relação com a implantação dos serviços de saúde - COELHO JÚNIOR, José Maria dos Santos (Universidade Federal do Pará, 2013)
Leprosy is an infectious disease caused by Mycobacterium leprae which constitutes serious public health problem in Brazil, mainly in the North. The annual detection rate of leprosy in children under 15 years is used by the Health Ministery of Brazil to assess the spreading of transmission in a given population. The study aimed to investigate and analyze the incidence of leprosy in children under 15 years in the city of Jacundá - Pará State, in a historical series (1999-2008) and its relation to the implantation of services of surveillance. The study found 210 cases that were reported during the period. The research was conducted in the information system database of Health department in the city searching for data from two instruments: Type of notification and follow-up report. It was observed that in the year followed by deployment of health services, an increase in the detection rate and the city remained hyperendemic in the last nine years of the series (> 1.0/ ten thousand inhabitants), however in the last three years, decline in the incidence presented with evidence that the deployment of new services contributed to the new scenario. Most patients included in the age group between 10 and 14 years (64.76%), male (50.5%), coming from the urban area (84.3%) with predominance of dimorphous (42 4%) at diagnosis. It was observed that according to the operational classification, the paucibacillary form was predominant (52,9%), which can be attributed to the improvement of the diagnosis in early stages. It was concluded, based on the gauge of the study, there is declining trend in the disease in the city.